Does the Role Checklist Measure Occupational Participation? - Tore Bonsaksen; Ursula Meidert; Deana Schuman; Hildegunn Kvarsnes; Lena Haglund; Susan Prior; Kirsty Forsyth; Takashi Yamada; Patricia J. Scott (Scholarworks @ WMU, 2015)
Background: Among the Model of Human Occupation (MOHO) assessments, the Role Checklist is one of the most established. In spite of its widespread use, no studies have examined role examples and their association with the three embedded levels of doing, as established in the MOHO theory. Method: A cross-sectional survey of 293 respondents from the US, the UK, Japan, Switzerland, Sweden, and Norway produced 7,182 role examples. The respondents completed Part I of the Role Checklist and provided examples of each internalized role they performed. Responses were classified as occupational skill, occupational performance, or occupational participation. Results: Thirty-three percent of the examples were classified as examples of occupational participation, whereas 65% were classified as examples of occupational performance. Four roles linked mostly with occupational participation, another four roles linked mostly with occupational performance, and the two remaining roles were mixed between occupational participation and occupational performance. Discussion: The Role Checklist assesses a person's involvement in internalized roles at the level of both occupational participation and occupational performance. There are differences among countries with regard to how roles are perceived and exemplified, and different roles relate differently to the occupational performance and occupational participation levels of doing. There are related implications for occupational therapists.